Quantum-Resistant Timestamping for Open Science: A Non-Technical Guide - Krägeloh, Christian; Bartholomew, Emerson J; Medvedev, Oleg N (Taylor and Francis Group, 2026)
Psychology faces a dual challenge from artificial intelligence (AI): While AI offers powerful research tools, it simultaneously threatens the discipline’s methodological foundations through deepfakes and synthetic data generation. The ability to prove when psychological data, preregistrations, and research protocols genuinely existed has become critical for maintaining scientific integrity, particularly as AI can now fabricate convincing retroactive evidence. These concerns are compounded by the vulnerability of existing open-science platforms to cyberattacks, data loss, or service unavailability, raising broader questions about the reliability and security of current research infrastructure. Together, these threats make robust, independent verification of research records increasingly urgent, especially in the context of psychology’s ongoing replication crisis and open-science reforms. This method article presents a quantum-resistant blockchain timestamping solution for researchers with no technical blockchain knowledge. Using the example of the Algorand blockchain’s Falcon cryptographic signatures – which are understood as being able to withstand both current AI threats and future quantum-computing attacks – we are demonstrating how researchers can create immutable proof that their hypotheses, data collection protocols, and datasets existed at specific times at the cost of a fraction of cent. Through step-by-step instructions, this article enables researchers to implement quantum-resistant timestamping regardless of their technical background. By removing barriers to blockchain-based verification, this method aims to make such protection as routine as current preregistration practices, ultimately establishing a new standard for safeguarding research integrity in the age of AI.
Keywords: Blockchain timestamping; research integrity; quantum-resistant cryptography; preregistration; open science